Validation of an ultrasound transducer's generation and receiving function on one single-mode fiber. (April 2020) - Guo, Xu; Wu, Nan; Zhou, Jingcheng; Du, Cong; Wang, Xingwei
Highlights: Combination of an ultrasound generator and a receiver on a single-mode fiber. The gold nanocomposite worked as the PA material and formed an FP interferometer. Tiny dimensions and potential to work in locations with very limited space. Abstract: This paper presents the design, fabrication and testing of a single-mode fiber optic ultrasound transducer. This transducer can work as an ultrasound generator and a receiver, based on principles of photoacoustic (PA) effect and Fabry–Pérot (FP) interference. PA effect is a process in which ultrasound waves are generated from optical energy by a PA material, and an FP structure is used for ultrasound receiving. The transducer was manufactured by coating a material called gold nanocomposite directly onto a single-mode optical fiber tip. The gold nanocomposite acted as the PA material and formed the FP structure as well. The transducer had the same size as the single-mode fiber, whose diameter was only 125 μm. It demonstrated its ability to generate ultrasound signals with a bandwidth of 5.6 MHz at an efficiency of 3.2 × 10 −5 and function as an ultrasound receiver with a sensitivity of 2.81 mV/MPa. The generator and receiver built together can currently only work separately. This new transducer has substantial potential to work in restricted space and harsh environments for non-destructive testing.